The Effect of the Implementation of Digitalization and Personal Technical Skills on Employee Work Effectiveness with the Perceiver Ease of Use System as a Moderation - Putri, Winny Novanda; Abriand, Abriand (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: Technology is increasingly developing over time and is certainly an attraction for companies to improve their image. Research Methodology: PT Jasa Armada Indonesia Tbk, quantitative questionnaires, Smart PLS 4, reviews and surveys used in this study. Without discussion or explanation. Results: The application of digitalization had a positive effect on employee work effectiveness. Limitations: There are variables that are less strong so that they can weaken employee work effectiveness but still have a positive value because the perceiver ease of the system can help employees work effectively. Contribution: PT Jasa Armada Indonesia Tbk.